Three new species of Grias (Lecythidaceae) from Colombia and Ecuador - Cornejo, Xavier; Prance, Ghillean T. (Phytotaxa, 2025)
Three new species of trees of Lecythidaceae are described for Colombia and Ecuador, Grias capparidastroides from the lowlands of the Cauca Department on the Pacific coast of Colombia, G. densiflora from the lowlands of the Antioquia Department in northwestern Colombia, and G. cryptica from Esmeraldas Province in northwestern Ecuador. The new species are formally described and illustrated, and their relationships with morphologically similar species are discussed.